Case Report: Anti-LGI1 Encephalitis Following COVID-19 Vaccination - Zlotnik, Yair; Gadoth, Avi; Abu-Salameh, Ibrahim; Horev, Anat; Novoa, Rosa; Ifergane, Gal (Frontiers in Immunology, 2022)
Anti-LGI1 autoimmune encephalitis (AE) is characterized by cognitive impairment or rapid progressive dementia, psychiatric disorders, faciobrachial dystonic seizures (FBDS) and refractory hyponatremia. Since December 2020, millions of people worldwide have been vaccinated against COVID-19. Several soft neurological symptoms like pain, headache, dizziness, or muscle spasms are common and self-limited adverse effects after receiving the COVID-19 vaccine. However, several major neurological complications, despite the unproven causality, have been reported since the introduction of the COVID-19 vaccine. Herein, we describe a 48 years old man presenting with rapidly progressive cognitive decline and hyponatremia diagnosed with anti LGI1 AE, occurring shortly after the second mRNA COVID -19 vaccination and possibly representing a severe adverse event related to the vaccination. Response to high dose steroid therapy was favorable. As millions of people worldwide are currently receiving COVID-19 vaccinations, this case should serve to increase the awareness for possible rare autoimmune reactions following this novel vaccination in general, and particularly of anti-LGI1 AE.